Jot: guiding journal selection with suitability metrics. - Gaffney, Stephen G.; Townsend, Jeffrey P. (Journal of the Medical Library Association, 2022)
Researchers grapple with a challenging and consequential decision each time they choose a journal for manuscript submission. There are several online tools that attempt to identify appropriate journals for a manuscript, but each of these tools has shortcomings in terms of the journal data they provide and the exploration functionality they offer--and not one of these tools is open source. Jot is a free and open-source web application that matches manuscripts in the fields of biomedicine and life sciences with suitable journals, based on a manuscript's title, abstract, and (optionally) citations. Jot gathers a wealth of data on journal quality, impact, fit, and open access options that can be explored through a dashboard of linked, interactive visualizations.